Application of modified tragus incision in temporomandibular joint disc anchoring surgery - GUO Yanjun; YAN Wei; CUI Zekun; CHEN Yong; WEN kai; HU Yaqi (Kouqiang hemian waike zazhi)
[Objective:] To introduce the surgical technique of temporomandibular joint disc anchoring through a modified tragus incision. [Methods:] From February 2017 to October 2021, 264 patients (328 sides of joints) with advanced anterior disc displacement without reduction (ADDWoR) admitted to our hospital were treated with temporomandibular joint disc anchorage using a modified tragus approach. The specific method was as follows: Use a modified intraauricular approach to separate the superficial temporal fascia and the deep and superficial layers of the deep temporal fascia, as well as the joint capsule, cut the joint capsule at the root of the zygomatic arch, expose the joint disc, using a Mini Mitek anchor screw to fix it at the posterior and lower pole of the condylar process, and using two Orthocor sutures for horizontal mattress suture to reposition the anterior displaced joint disc. Magnetic resonance imaging (MRI) of the temporomandibular joint was performed before and within 7 days after surgery. The facial nerve condition was observed from 1 to 7 days after surgery, follow-up MRI was performed 3 months after surgery, and the mouth opening degree was recorded at 1 week, 1 month, and 3 months after surgery. The visual analog scale (VAS) was used to record the relief of temporomandibular joint pain in patients at 3 months after surgery. The vancouver scar scale was used to evaluate the scar condition in the surgical area at 3 months after surgery. [Results:] According to the evaluation of postoperative MRI, 306 joints (249 cases) were evaluated as "excellent", 20 joints (14 cases) were evaluated as "good", and 2 joints (one case) were evaluated as "poor". The successful reduction rate was 99.39% (326/328 sides). Only one patient evaluated as "poor" after surgery, accounting for 0.61% (2/328 sides). At the 3-month follow-up after surgery, all patients showed improvement in limited mouth opening, with pain scores below 2 and scar evaluations below 3. [Conclusion:] Improving the concealed position of the incision inside the tragus and achieving good results in the reduction of the temporomandibular joint disc is a widely applicable surgical approach for temporomandibular joint disc anchoring.